Dengue: educar para prevenir - CHAVES, Maria Auxiliadora (2024)
Dengue is an infectious disease transmitted by the bite of the female mosquito Aedes aegypti. It is a major public health problem. Therefore, to guide this research were evaluated educational interventions conducted in some schools of the City of Abaetetuba-Pa, to verify the existence of relationship between acquired knowledge and practices regarding the prevention of Dengue by the students. In this sense there was knowledge of students through questionnaires in the classroom on the issue of Dengue in Abaetetuba. This study was conducted in five (5) public schools of the City of Abaetetuba - PA. Two questionnaires were used: one for students (400) and another for teachers (08) of these schools. In the analysis of student data were assembled comparative graphs between sets and schools, which revealed that still need to discuss much about the topic as well as bringing environmental education into the schools. The sixth graders were unable to recognize the disease, however the seventh year students highlighted the disease and its transmission. Already the eighth graders had difficulty responding to questions, however, the analysis revealed that the ninth grade students were able to correlate the disease, its transmission and the main care to avoid it. The analysis of teachers revealed that many teachers have difficulty working the issue, due to lack of instrumentation that few schools have, yet the vast majority considers a multiplier of actions to combat dengue in school and in the classroom. So, are important educational aiming to bring health problems and environmental education at schools, where teachers and students feel involved in the control and prevention of dengue.